Polymorphisms of the adiponectin gene in gestational hypertension and pre-eclampsia - Machado, J S R; Palei, A C T; Amaral, L M; Bueno, A C; Antonini, S R; Duarte, G; Tanus-Santos, J E; Sandrim, V C; Cavalli, R C (Springer Nature, 2013)
Adiponectin is a hormone involved in energy homeostasis by regulating glucose and lipid metabolism. In addition, the adiponectin gene (ADIPOQ) has polymorphisms that can modulate the circulating concentration of adiponectin. Abnormal adiponectin levels have been associated with pre-eclampsia (PE); however, the influence of genetic polymorphisms on the development of hypertensive disorders of pregnancy is unclear. The aim of this study was to examine whether ADIPOQ polymorphisms are associated with gestational hypertension (GH) and/or PE. We studied 401 pregnant women: 161 healthy pregnant (HP), 113 pregnant with GH and 127 pregnant with PE. ADIPOQ polymorphisms -11391G>A (rs17300539), -11377C>G (rs266729), 45T>G (rs2241766) and 276G>T (rs1501299) were genotyped by allelic discrimination assays using real-time PCR. Haplotypes were inferred using the PHASE 2.1 program. We observed that the genotypic frequencies of the -11377C>G polymorphism were different in PE compared with HP (P<0.0125), with the CT genotype being more commonly found in PE patients than in HP women (P<0.0125). However, allelic frequencies of this single-nucleotide polymorphism were similar between PE and HP (P>0.0125). No difference was observed when GH and HP groups were compared (both P>0.0125). In addition, we found no difference in genotype or allele distributions for the -11391G>A, 45T>G and 276G>T polymorphisms when we compared GH or PE with HP (all P>0.0125). In conclusion, we found a modest association between the CG genotype of the -11377C>G polymorphism and PE.Journal of Human Hypertension advance online publication, 27 June 2013; doi:10.1038/jhh.2013.53.